2008
DOI: 10.1007/s00128-008-9370-4
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers in Human Serum and Sperm Quality

Abstract: Polybrominated diphenyl ethers (PBDEs) are widely used flame retardants; currently, they are identified as ubiquitous environmental contaminants. Several studies indicate that PBDEs might affect male fertility. We present the results of a pilot study on the relationship between human serum PBDEs and sperm quality. The PBDE levels in Japan are comparable to those found in European countries. Strong inverse correlations were observed between the serum concentration of 2,2′,4,4′,5,5′-hexabromodiphenyl ether and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 13 publications
2
73
0
Order By: Relevance
“…Effects of PBDEs in animal models include endocrine disruption, neurodevelopmental and behavioural effects, hepatic abnormalities, and possibly cancer (McDonald, 2002;Birnbaum and Staskal, 2004;Darnerud, 2008). Although little human epidemiology has yet been done, early studies suggest effects on male reproductive hormones (Meeker et al, 2009) and fertility (Akutsu et al, 2008b), thyroid hormone homeostasis (Turyk et al, 2008), cryptorchidism (Main et al, 2007), and lower birth weight and length (Chao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of PBDEs in animal models include endocrine disruption, neurodevelopmental and behavioural effects, hepatic abnormalities, and possibly cancer (McDonald, 2002;Birnbaum and Staskal, 2004;Darnerud, 2008). Although little human epidemiology has yet been done, early studies suggest effects on male reproductive hormones (Meeker et al, 2009) and fertility (Akutsu et al, 2008b), thyroid hormone homeostasis (Turyk et al, 2008), cryptorchidism (Main et al, 2007), and lower birth weight and length (Chao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to toxicity for male reproduction, Main et al (2007) found significantly higher ΣPBDEs concentrations in the breast milk of nursing mothers of boys with cryptorchidism than in the nursing mothers of boys not affected by the disorder, and they also found that ΣPBDEs in breast milk associates positively with the serum of luteinizing hormone. Serum BDE-153 in male adults (n = 10) is inversely correlated with semen quality and testes size (Akutsu et al, 2008). In an American study in Massachusetts (Meeker et al, 2009), a study recruited 24 nonsmoking men age 18-54 to investigate house dust PBDE concentrations.…”
Section: Pbdes and Reproductionmentioning
confidence: 99%
“…A summary of published epidemiological investigations into the effects of PBDEs on semen quality or sex hormones is listed in Table 1. In a pilot study on 45 young Japanese males, a simple linear regression model was used to show a strong inverse correlation between the concentration of 2,2′,4,4′,5,5′-hexabromodiphenyl ether (BDE-153) in sperm and total sperm concentration (r = -0.841, p = .002) and testis size (r = -0.764, p = .01) (Akutsu et al, 2008). A cross-sectional study on American men reported a robust inverse relationship between PBDE levels in house dust and serum concentrations of luteinizing hormone (LH) and FSH, and a positive association between PBDEs and sex hormone-binding globulin (SHBG) (Meeker et al, 2009).…”
Section: Polybrominated Diphenyl Ethersmentioning
confidence: 99%